2005
DOI: 10.1111/j.1365-2672.2005.02720.x
|View full text |Cite
|
Sign up to set email alerts
|

Sampling methodologies and dosage assessment techniques for submicrometre and ultrafine virus aerosol particles

Abstract: Aims:The aerosolization and collection of submicrometre and ultrafine virus particles were studied with the objective of developing robust and accurate methodologies to study airborne viruses. Methods and Results: The collection efficiencies of three sampling devices used to sample airborne biological particles -the All Glass Impinger 30, the SKC BioSamplerÒ and a frit bubbler -were evaluated for submicrometre and ultrafine virus particles. Test virus aerosol particles were produced by atomizing suspensions of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
239
3

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 197 publications
(261 citation statements)
references
References 48 publications
19
239
3
Order By: Relevance
“…Third, the particle collection efficiency of the SKC BioSampler decreases from about 96% for 1 μm aerosol particles to about 50% for 0·3 μm particles and 10% for 0·1 μm particles 32, 33, 34. Thus, many of the smallest particles carrying influenza virus may not have been collected in our experiments.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Third, the particle collection efficiency of the SKC BioSampler decreases from about 96% for 1 μm aerosol particles to about 50% for 0·3 μm particles and 10% for 0·1 μm particles 32, 33, 34. Thus, many of the smallest particles carrying influenza virus may not have been collected in our experiments.…”
Section: Discussionmentioning
confidence: 96%
“…Aerosol particles were collected using an SKC BioSampler with a 5‐ml vessel (#225‐9593, SKC) containing 5 ml of viral transport media (VTM) consisting of Hank's balanced salt solution (HBSS; Invitrogen) supplemented with 0·1% bovine serum albumin (BSA; Sigma‐Aldrich), 100 units/ml penicillin G, and 100 units/ml streptomycin (Invitrogen). The particle collection efficiency for the SKC BioSampler (i.e., the percentage of particles of a given size that are collected by the sampler) is approximately 10% for particles with aerodynamic diameters of 0·1 μm; 50% for 0·3 μm particles; 96% for 1 μm particles; 100% for 2 μm particles; and 50% for 8 μm particles 32, 33, 34. Particles larger than 10–15 μm are expected to be removed by the sampler elbow and not collected.…”
Section: Methodsmentioning
confidence: 99%
“…2 assumes an AGI-30 collection efficiency (E) of 100%. It has been shown that E can be < 10% in the 10-300 nm size range (20) ; however, given that E would appear in both the numerator and denominator of Eq. 4, it will cancel out and thus have no effect on PEN results.…”
Section: Aerosol Sampling Physical Penetrationmentioning
confidence: 99%
“…It has been observed that viable MS2 virions are present in aerosol particles from 25 to 407 nm in diameter. (20) …”
Section: Physical Penetrationmentioning
confidence: 99%
See 1 more Smart Citation